Gnss blind interference detection based on fourth-order autocumulants - Nunes, Fernando (2018)
GNSS signals affected by additive channel noise are approximately Gaussian, but often the presence of interference may change that distribution.We propose a blind detection method based on the Giannakis-Tsatsanis Gaussianity test to evaluate the presence of narrowband and wideband non-Gaussian interference. This method, resorting to the sample fourth-order autocumulants, is compared to other Gaussianity tests. The asymptotic covariance matrix of the estimated autocumulant vector is analytically determined, thus reducing the complexity of the proposed technique.